2005
DOI: 10.1530/eje.1.01934
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ghrelin in thyroid dysfunction is related to insulin resistance and not to hunger, food intake or anthropometric changes

Abstract: Objective: Ghrelin is a gastric peptide that plays a role in appetite stimulation, energy balance and possibly in insulin resistance. Hyperthyroidism is a situation where negative energy balance and insulin resistance coexist, while in hypothyroidism a positive energy balance and normal insulin sensitivity predominate. We investigated ghrelin levels and their relationship with hunger, food intake and both anthropometric and insulin resistance parameters in patients with thyroid dysfunction. Design and methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 38 publications
7
57
2
Order By: Relevance
“…In contrast, other studies have found ghrelin levels in hypothyroid patients to be similar to those of healthy subjects and there was no significant change in ghrelin levels after medical treatment of hypothyroidism (Gimenez-Palop et al, 2005;Sadegholvad et al, 2007;Tanda et al, 2009). Anti-parietal cell antibodies and atrophic gastritis has been M a n u s c r i p t 22 detected in patients with autoimmune thyroid disease (Centanni et al, 1999).…”
Section: Page 21 Of 44mentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, other studies have found ghrelin levels in hypothyroid patients to be similar to those of healthy subjects and there was no significant change in ghrelin levels after medical treatment of hypothyroidism (Gimenez-Palop et al, 2005;Sadegholvad et al, 2007;Tanda et al, 2009). Anti-parietal cell antibodies and atrophic gastritis has been M a n u s c r i p t 22 detected in patients with autoimmune thyroid disease (Centanni et al, 1999).…”
Section: Page 21 Of 44mentioning
confidence: 94%
“…Insulin resistance is increased in hyperthyroidism (Gimenez-Palop et al, 2005) and hyperinsulinaemia has been shown to suppress ghrelin levels (Saad et al, 2002) regardless of thyroid status (Riis et al, 2003).…”
Section: Page 21 Of 44mentioning
confidence: 99%
“…The relationship between thyroid cancer pathogenesis and ghrelin and obestatin expression has not been clearly defined. Furthermore, since the function of thyroid gland is associated with the maintenance of energy balance, the relationship between ghrelin, obestatin and thyroid function is worthy of consideration [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating ghrelin levels are reduced in hyperthyroid patients [157,[207][208][209][210][211]. On the other hand, ghrelin levels were elevated in hypothyroid patients in some reports [212,213], but not in others [207,211,214].…”
Section: Thyroid Hormonementioning
confidence: 98%